Clinical profile and risk factors of enuresis in children - Pyarejan, Karamath S.; Muthiah, Ravisankar (International Journal of Contemporary Pediatrics, 2020)
Background: Enuresis is a common problem in children and its incidence is multifactorial in nature. The aim of this study is to assess the etiological risk-factors in enuresis in the study population and also to compare the risk factors in enuresis subgroups. Methods: A total of 51 patients with enuresis presenting to the department of paediatrics, Institute of Social Paediatrics, Govt. Stanley Hospital, Chennai were included in the study. All children were sub classified as primary/secondary and the primary enuretics were sub classified into monosymptomatic/non monosymptomatic depending on the symptoms. The data was analyzed and the results presented. Results: Enuresis was common in boys. Statistically significant difference in the incidence of disorder between primary and secondary enuretic children was seen in relation to presence of storage symptoms (p=0.04), cystitis (p=0.013) sleep disordered breathing (p=0.0001) and low-income status (p=0.04). No statistically significant difference between into monosymptomatic nocturnal enuresis (MNE) and non-monosymptomatic nocturnal enuresis (NMNE) children was observed in terms of gender, difficulty in arousal, specific gravity, spina bifida, low bladder capacity and family history (p>0.05). Conclusions: The findings of the study reported that risk factors related to the incidence is similar in both primary and secondary enuresis. MNE and NMNE have no differences in the presentation and probably represent the spectrum of a same disorder.